PROTEIN FRACTIONATION AND UTILIZATION OF SOYBEAN AND REDBEAN AS AFFECTED BY DIFFERENT DRYING TEMPERATURE - Anuraga Jayanegara; Yesi Chwenta Sari; Roni Ridwan; Didid Diapari; Erika Budiarti Laconi (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
The objective of this study was to investigate the influence of different drying temperature on chemical composition, in vitro rumen fermentation and digestibility of soybean and redbean. Soybean and redbean were dried in an oven set at four different drying temperatures, i.e. 50, 60, 70 and 80 oC for 24 h in three replicates. Dried samples were then milled and used further for chemical composition determination (proximate analysis, Van Soest analysis and protein fraction) and in vitro rumen fermentation assay. Parameters measured in the in vitro assay were gas production, digestibility, pH, ammonia and volatile fatty acids (VFA). Data obtained were analyzed by using analysis of variance and a posthoc test namely Duncan’s multiple range test. Results revealed that neutral detergent insoluble crude protein (NDICP) content increased at higher drying temperature (70 or 80 oC) for both soybean and redbean (P<0.05) but at different magnitude. As with NDICP, higher temperature led to a higher acid detergent insoluble crude protein (ADICP) both in soybean and redbean (P<0.05). Higher temperature decreased gas production rate (GPR) of both beans (P<0.05). Drying of soybean at 70 or 80 oC decreased crude protein digestibility (CPD) of soybean than dried at 50 or 60 oC (P<0.05). Higher drying temperature resulted in a lower NH3 concentration (P<0.05). It can be concluded that drying temperature at 50 or 60 oC is safe to maintain nutritional quality of soybean and redbean.